Analisis Perbandingan Pembayaran Tunai dan QRIS Dalam Melakukan Transaksi Dikalangan Mahasiswa Serang Banten - Aulia Syahda; Diva Nurul Aida; Wahyu Hidayat; Zaini Ibrahim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Before the development of science and technology, the payment system in Indonesia was only done using cash. Money is used to make daily human payments as a medium of exchange. Cash payment instruments are regulated in Law Number 7 of 2011 concerning Currency. But along with the development of science and technology, payment instruments have been more widely used. This progress comes in the form of digital payment instruments. QRIS is one of the digital payments available today. QRIS stands for Indonesian Quick Response Code Standard launched by Bank Indonesia. When making payments through QRIS as a means of payment, you can use one e-wallet to pay merchants, such as Link Aja, Gopay, OVO, DANA, Shopeepay, and others. This research was conducted to compare payment systems (cash and QRIS payments) made by Banten students in making transactions. This research was conducted using quantitative methodology. The distribution data was collected through the distribution of questionnaires.